Strike the hammer : the Black freedom struggle in Rochester, New York, 1940-1970 - Hill, Laura Warren (Cornell University Press, 2021)
"This book explores the rise of the Black Freedom Struggle in Rochester, NY across the mid-twentieth century. It examines Black migration, politics, rebellions, organizing, and capitalism"-- Provided by publisher.
Keywords: African Americans -- Civil rights -- New York (State) -- Rochester -- History -- 20th century.; Civil rights movements -- New York (State) -- Rochester -- History -- 20th century.; Black power -- Economic aspects -- New York (State) -- Rochester.; Black power -- New York (State) -- Rochester -- History -- 20th century.; Rochester (N.Y.) -- Race relations -- History -- 20th century.; Rochester (N.Y.) -- Race relations -- Economic aspects.; Noirs américains -- Droits -- New York (État) -- Rochester -- Histoire -- 20e siècle.; Mouvements des droits de l'homme -- New York (État) -- Rochester -- Histoire -- 20e siècle.; Black power -- Aspect économique -- New York (État) -- Rochester.; Black power -- New York (État) -- Rochester -- Histoire -- 20e siècle.; HISTORY / United States / State & Local / Middle Atlantic (DC, DE, MD, NJ, NY, PA); African Americans -- Civil rights; Black power; Civil rights movements; Race relations; Race relations -- Economic aspects; New York (State) -- Rochester; 1900-1999; Black Freedom Struggle in Rochester, Corporate Responsibility in the era of Black Power, Paths to Black economic development, Police brutality in Rochester, 1964 Black Uprising in Rochester.; Electronic books.; History